1975
DOI: 10.1159/000178671
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Lesions of Streptozotocin Diabetic Rats

Abstract: Diabetes was induced in adult male albino rats by a single intravenous injection of streptozotocin (75 mg/kg body weight). The diabetes was allowed to stabilize for at least 15 days, whereafter the testicular and seminal vesicle histology was studied at various time intervals. Reduction in testis weights and tubule diameters was significant after 2 weeks of diabetes. The changes in seminiferous tubules ranged from premature sloughing of epithelium to total cessation of spermatogenesis. The testicular histology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
54
1
2

Year Published

1979
1979
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 8 publications
8
54
1
2
Order By: Relevance
“…Among other complications, impairment of testicular function and fertility occurs in these diabetic animals: a spermatogenic arrest at step 7 spermatids was seen similar to that found in hypophysectomized animals [2]. Diminution of testicular androgen production in vivo as well as in vitro (incubation of interstitial cells) was described for streptozotocin-diabetic rats [3,4].…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Among other complications, impairment of testicular function and fertility occurs in these diabetic animals: a spermatogenic arrest at step 7 spermatids was seen similar to that found in hypophysectomized animals [2]. Diminution of testicular androgen production in vivo as well as in vitro (incubation of interstitial cells) was described for streptozotocin-diabetic rats [3,4].…”
supporting
confidence: 62%
“…(2) are there additional disturbances within the steroidogenic pathways which could also be responsible for diabetic testicular injury?…”
mentioning
confidence: 99%
“…Several studies have demonstrated a stepwise decrease in mean testosterone level per progressive increase in fasting plasma glucose throughout the whole range of plasma glucose [60,62,63]. In laboratory animals, diabetes has been associated with reductions in testicular Leydig cell number [66,67,68] and in testosterone secretion [68,69], possibly due to a direct adverse effect of glycaemia [68].…”
Section: Discussionmentioning
confidence: 99%
“…The existence of specific insulin receptors in Leydig cells has been demonstrated, as has a decrease in these receptors in diabetic animals [25]. The seminiferous tubules of diabetic rats undergo degenerative changes until spermatogenesis is arrested [29] with a corresponding decrease in the production of CO, from glucose by the sperm and seminiferous tubules [ 121. In summary, future work should be directed toward clarifying the influence of diabetes mellitus and insulin on the function of the seminiferous tubule, testicular steroidogenesis, and its hypothalamichypophyseal control.…”
Section: Discussionmentioning
confidence: 99%